2014
DOI: 10.1587/comex.3.27
|View full text |Cite
|
Sign up to set email alerts
|

On the tracking performance of least squares MIMO channel estimation in rician fading

Abstract: Abstract:The tracking Mean Square Error (MSE) of the least squares (LS) Multiple Input Multiple Output (MIMO) channel estimation in rician flat fading channel is derived in closed-form, which is then verified by Monte Carlo simulation. The channel accomodates applications where the elevation angle between the transmitter and the receiver dictates the doppler shift of the Line of Sight (LOS) component, as encountered in communications from satellite or High Altitude Platform (HAP) to a moving mobile. A higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(30 citation statements)
references
References 6 publications
2
28
0
Order By: Relevance
“…Zakia, et al have shown that for a moving receiver, the Doppler shift of the LOS channel component ( d 90°) yields worse MSE tracking performance at the receiver [6]. Specifically, the MSE tracking gain achieved when the mobile travels from 0° to 60° is insignificant if compared to when it travels to a 90° elevation angle.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Zakia, et al have shown that for a moving receiver, the Doppler shift of the LOS channel component ( d 90°) yields worse MSE tracking performance at the receiver [6]. Specifically, the MSE tracking gain achieved when the mobile travels from 0° to 60° is insignificant if compared to when it travels to a 90° elevation angle.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Faletti, et al [2] have implemented the multiple-input multiple-output (MIMO) beamforming recursive least-squares (RLS) algorithm, while examples of single-input multiple-output (SIMO) are given by White, et al in [4] and Zakia, et al In [5], the recursive LS (RLS) MIMO channel estimation algorithm for Rician fading was proposed by Zakia, et al [6] as a generalization to the Rayleigh fading case given in Karami [7]. Both papers present closed-form solutions on the tracking performance in terms of mean square error (MSE).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations